Bone Mineral Density Evaluation in Four Different Occupational Groups - Mustafa Turgut Yıldızgören; Ali Erdem Baki; Timur Ekiz; Pınar Küçük Eroğlu; Engin Tutkun; Hınç Yılmaz (Galenos Yayinevi, 2015)
Objective: The aim of this study was to evaluate bone mineral density (BMD) and to discuss the potential risk factors for osteoporosis in four different occupational groups. Materials and Methods: In this study, 100 males who were admitted to our clinics for their periodic occupational controls and 40 healthy subjects were included. Demographic features of the participants were recorded. BMD was evaluated by Dual-energy x-ray absorptiometry (DXA) from lumbar vertebrae and proximal femur. Results: Participants were mainly from the following four occupational groups; accumulator manufacturers (n=30, 21.4%), painting workers (n=30, 21.4%), welders (n=15, 10.7%), and quartz miners (n=25, 17.9%) sectors. In addition, there were 40 healthy subjects (28.6%). Compared with the control group, femoral neck T-scores (p=0.023) and Z-scores (p=0.031) were significantly lower in miners. L2-L4 BMD values were significantly lower in accumulator manufacturers (p=0.041) and quartz miners (p=0.022) as compared with the control group. Conclusion: Workers in the accumulator and mining sectors had lower BMD than control subjects. Clinicians should keep in mind occupational risk factors related with chemical exposure for osteoporosis while questioning osteoporosis risk factors. (Turkish Journal of Osteoporosis 2015;21: 19-22)